Structure of inclusion complex of disulfiram with hydroxypropyl-β-cyclodextrin - V. S. Tyukova; S. A. Kedik; A. V. Panov; V. V. Bondar; A. I. Lavrentieva (Тонкие химические технологии)
Disulfiram is an inhibitor of superoxide dismutase, reduced lipid peroxidation, and can be an effective pharmaceutical substance for the treatment of cataracts. Unfortunately, the use of disulfiram in ophthalmology is limited due to its practically insoluble in water. Hydroxypropyl-β-cyclodextrin is an effective solubilizing agent and has long been used in the pharmaceutical industry. Due to its structure hydroxypropyl-β-cyclodextrin forms inclusion complexes with pharmaceutical substance which soluble in water is limited. In this paper it was investigated a new method of obtaining inclusion complex of hydroxypropyl-β-cyclodextrin with disulfiram. Inclusion complex prepared and isolated in powder form, the formation of inclusion complex and its physicochemical properties was confirmed by X-ray powder diffraction and UVspectrophotometry.